Development of Latent Fingerprints on Various Surfaces- A Review - Manasi P. Bhosale; Manjushree S. Bagul (International Journal of Scientific Research in Science and Technology, 2024)
In recent times the fingerprints are obtained as key evidence from various crime scenes. This plays a vital role in solving the crime. Fingerprint development on various surfaces by powder method is very easy method for latent fingerprint visualization. Numerous techniques have been documented in the literature for revealing latent fingerprints on a variety of surfaces. In this present review paper, powders rather than standard powders are used for fingerprint development. Fingerprints have been developed on various surfaces using turmeric powder, soil, silica gel G powder, etc. Development of fingerprint on challenging surfaces is difficult. Powders used for fingerprint development is expensive so some easily available, inexpensive, eco-friendly powders are studied in this review.
Keywords: Evidence; Fingerprint Development; Standard Powders; Turmeric Powder; Soil; Silica Gel G Powder; Eco-Friendly